Performance analysis and evaluation of a 10.6 kWp grid-connected photovoltaic system in Serpong. Issue 1 (December 2020) - Nurdiana, E; Subiyanto, I; Indarto, A; Riza,; Wibisono, G; Hudaya, C
Abstract: The grid-connected Photovoltaic (PV) System was installed in the rooftop of Energi Building, PUSPIPTEK in 2017 located in Serpong, South Tangerang. The System consists of 40 modules @265 Wp, a 10 kWh battery system, and a 10250 kW grid-tie inverter. This study presents the performance analysis of the PV system based on the eight-months monitored data from July 2019 to February 2020. The evaluated parameters of the PV system include yields, performance ratio, capacity factor, energy efficiency, and average daily energy output of the PV system. The results show that the average value of the performance ratio and capacity factor during the eight-months monitored period were 82.42% and 14.07% with average values of the array ( Ya ), final ( Yf ) and reference ( Yr ) yields were 3.49 kWh/kWp/d, 3.38 kWh/kWp/d, and 4.12 kWh/kWp/d, respectively. Meanwhile, the average daily energy output of the PV system during the eight-months monitored period was 36.92 kWh per day with the average values of the module ( ƞPV ), system ( ƞsys ), and inverter ( ƞinv ) efficiency was found to be 15.29%, 14.77%, and 96.63%, respectively. Compared with previous studies in the literature, these results indicated that the grid-connected PV system installed in Energi Building PUSPIPTEK Serpong exhibited good performance.